When Do Secondary Markets Harm Firms? - Chen, Jiawei; Esteban, Susanna; Shum, Matthew (American Economic Review, 2013)
To investigate whether secondary markets aid or harm durable goods manufacturers, we build a dynamic model of durable goods oligopoly with transaction costs in the secondary market. Calibrating model parameters using data from the US automobile industry, we find the net effect of opening the secondary market is to decrease new car manufacturers' profits by 35 percent. Counterfactual scenarios in which the size of the used good stock decreases, such as when products become less durable, when the number of firms decreases, or when firms can commit to future production levels, increase the profitability of opening the secondary market. (JEL L13, L25, L62, L81)